2021
DOI: 10.3390/diagnostics11101871
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Sequencing of Cerebrospinal Fluid B Cell Repertoires in Multiple Sclerosis and Other Neuro-Inflammatory Diseases—A Comprehensive Review

Abstract: During the last few decades, the role of B cells has been well established and redefined in neuro-inflammatory diseases, including multiple sclerosis and autoantibody-associated diseases. In particular, B cell maturation and trafficking across the blood–brain barrier (BBB) has recently been deciphered with the development of next-generation sequencing (NGS) approaches, which allow the assessment of representative cerebrospinal fluid (CSF) and peripheral blood B cell repertoires. In this review, we perform lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…An alternative function of B cells could be centered around antigen presentation and T cell stimulation. Our group ( Kowarik et al, 2021 ) and other studies ( Stern et al, 2014 ; Ruschil et al, 2021 ) have demonstrated that B cells not only traverse the blood-brain barrier but also recirculate in the peripheral blood through cervical lymph node drainage ( Figure 1 .). B cells, potentially primed against antigens in the CNS compartment during relapse, could thus possess the capacity to re-enter germinal centers in the periphery and perpetuate autoimmune circuits ( Ruschil et al, 2021 ).…”
Section: B Cells In Multiple Sclerosismentioning
confidence: 54%
See 1 more Smart Citation
“…An alternative function of B cells could be centered around antigen presentation and T cell stimulation. Our group ( Kowarik et al, 2021 ) and other studies ( Stern et al, 2014 ; Ruschil et al, 2021 ) have demonstrated that B cells not only traverse the blood-brain barrier but also recirculate in the peripheral blood through cervical lymph node drainage ( Figure 1 .). B cells, potentially primed against antigens in the CNS compartment during relapse, could thus possess the capacity to re-enter germinal centers in the periphery and perpetuate autoimmune circuits ( Ruschil et al, 2021 ).…”
Section: B Cells In Multiple Sclerosismentioning
confidence: 54%
“…Double negative (DN) B cells constitute another B cell population that lacks expression of immunoglobulin D and CD27 surface markers and has shown to be associated with autoimmune diseases ( Sanz et al, 2019 ; Ruschil et al, 2021 ). The class-switched IgD- phenotype may indicate an antigen-specific maturation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we could show that multiple treatments including dimethyl fumarate, interferon beta and fingolimod all lead to a significantly decreased peripheral blood memory B cell fraction ( 36 ) pointing at a pathophysiologic role of memory B cells in MS. An overall pathophysiological role of peripheral blood B cells is strongly supported by the high efficacy of peripheral B cell depleting anti CD20 antibodies that are supposed to enter the CNS in limited concentrations ( 35 , 37 ). Given the strong evidence for an intrathecal B cell activation and expansion ( 4 ), it was surprising that intrathecal rituximab treatment did not show substantial better effects than peripheral B cell depletion ( 37 ). However, it has to be noted that intrathecal effects of rituximab might be hampered by the lack of intrathecal complement and the consecutively limited effects regarding B cell depletion.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, B cells have been proven to play an important pathophysiological role in multiple sclerosis (MS) and B cells have more and more entered into the focus of therapeutic approaches ( 1 , 2 ). Although several targets including recent work on possible Epstein-Barr virus (EBV) antigens have been suggested as potential B cell antigens during MS pathophysiology ( 3 ), the exact role of B cells in MS remains inconclusive ( 4 ). Besides a primary antigen driven role of B cells in MS it has to be taken into consideration that B cells might also serve as antigen presenting cells, produce proinflammatory cytokines and thus might feed autoimmune circuits in the periphery ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation